Synthesis, structural and optical properties of Cr doped ZnO nanoparticles - Ali Ansari, Sajid; Khan, Wasi; Chaman, M.; Naqvi, A.H. (Asian Journal of Chemistry, 2011)
Nanosized Cr-doped ZnO particles were synthesized by facile sol-gel method. The structural and optical properties of the particles have been investigated by XRD and FTIR spectroscopy at room temperature for 0, 1 and 5 % concentration of Cr doping. X-ray diffraction analysis reveals that the Cr-doped ZnO crystallizes in a single phase polycrystalline nature with wurtzite lattice. The average crystallite size decreases with increase in Cr concentration (i.e. 33.5 nm for 0 % & 29.7 nm for 1 % and 24.7 for 5 %). FTIR results also indicate the correlation between structural and optical properties of the nanoparticles.